Comparative study on registration application of proprietary Chinese medicine in the Guangdong-Hong Kong-Macau Greater Bay Area of China - Zicheng Liu; Jinmin Zhao; Yitao Wang; Hua Luo (Taylor & Francis Group, 2024)
ABSTRACTBackground Proprietary Chinese medicine (PCM) is widely used in the Guangdong-Hong Kong-Macau Greater Bay Area (GBA) of China. However, the regulatory frameworks and procedures for PCM registration in the region are not well-established, and there are differences among the three jurisdictions. The study is aimed to compare the legal basis, regulatory guidelines, application requirements, and evaluation criteria in each jurisdiction.Methods We conducted a comprehensive review of the registration application processes for PCMs in the Chinese mainland, Hong Kong, and Macau based on publicly available information from respective regulators.Results The study found that the registration application process in the GBA was complex and time-consuming, with differences in requirements and procedures among the three jurisdictions. The study also identified several challenges faced by PCM manufacturers, such as the lack of harmonisation of regulatory requirements and procedures and the requirement of package inserts and labelling for PCM products. The study proposed recommendations for improving the registration process and promoting the development of the PCM industry in the GBA.Conclusion This study provides a comprehensive understanding of the PCM product license application procedures and requirements in the GBA, coupled with discernment of their similarities and disparities, equips applicants with the knowledge to formulate an appropriate strategy for obtaining product approval. Exploring potential methods for harmonising the regulatory process stands to benefit manufacturers, regulators, and patients by improving efficiency and curtailing costs.